2011
DOI: 10.3727/096368910x546553
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of T-Cell Proliferation by Murine Multipotent Mesenchymal Stromal Cells is Mediated by CD39 Expression and Adenosine Generation

Abstract: Multipotent mesenchymal stromal cells (MSCs) are bone marrow-derived cells of nonhematopoietic origin with immunoregulatory properties. Although some functions of MSCs have been identified, there are still features that are not explained thus far. The aim of the present study was to identify novel factors involved in MSC-mediated inhibition of T-cell proliferation. We here demonstrate that the surface molecule CD39 is coexpressed in concert with CD73 on murine MSCs catalyzing the generation of adenosine, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
76
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(78 citation statements)
references
References 61 publications
(89 reference statements)
0
76
1
1
Order By: Relevance
“…Adding a parenthesis to this subject, CD39 expression by MSCs has been subject to conflicting observations [177]. In contrast to our observations [175] and others [178,179], some authors describe a lack or low CD39 expression by MSCs [176,180]. In our view, this might be due to specific experiment design or to antibody variation.…”
Section: Mscs and Adenosinecontrasting
confidence: 55%
“…Adding a parenthesis to this subject, CD39 expression by MSCs has been subject to conflicting observations [177]. In contrast to our observations [175] and others [178,179], some authors describe a lack or low CD39 expression by MSCs [176,180]. In our view, this might be due to specific experiment design or to antibody variation.…”
Section: Mscs and Adenosinecontrasting
confidence: 55%
“…In line with this investigation, recent studies provided evidences that CD39 mediated the immune suppression of T cells by MSCs in a cell-to-cell contact manner [8,9]. Adenosine is an anti-inflammatory product of enzymatic hydrolysis of extracellular ATP by CD39 (ectoATPase) and CD73 (ecto-5′-AMP nucleotidase).…”
Section: Introductionmentioning
confidence: 58%
“…Recently, some studies have shown that murine MSCs could share the adjacent modulatory function of inflammatory immune responses with Treg cells through the mediation of the CD39/CD73 pathway [8,9]. CD39 is an extracellular enzyme that catalyzes ATP and ADP to AMP, followed by rapid dephosphorylation of AMP into adenosine by CD73.…”
Section: Discussionmentioning
confidence: 99%
“…Adenosine is readily formed from ATP by the sequential activity of CD39 and CD73 ectoenzymes, which are expressed on the MSC plasma membrane [27,28,[72][73][74]. When we tested ectonucleotidase expression, we found that more than 90% of BM-hMSCs were CD73 positive, whereas CD39 was expressed in a median of 25.6% of the cells (range: 14.8%-59.9%) (Supplementary Table S4).…”
Section: Bm-hmsc Differentiation Is Regulated By Different Signaling mentioning
confidence: 99%